Extortion in Colombia 2003 - 2015 (2018)
Extortion is the crime that has had the biggest growth in Colombia in the past few years, and it is among those that most affect the security perception in the country. Between 2003 and 2014 this crime grew by 136%, affecting all the departaments and 901 municipalities in the country, that is 81% of the municipalities, 70% of the reported extortion extortion cases concentrated in 57 municipalities whit over 100 thousand inhabitants. Common criminals were responsible for 74% of the cases, guerrillas for 11%, and the Bacrim for 5%, perpetrators of the 11per cent remaining cases could not be established. It is important to note that the black figure of this crime, i.e. cases ocurred but not reported, is one of the highest, in the criminal spectrum, and it is estimated to be around 80%. However, it is important to emphasize that between 2003 and 2010 extortion decreased in the country by 34%. It is as of 2010 that this crime reaches its biggest grwth. In fact, between 2010 and 2014 represent 46% of all cases in the last twelve years. By far 2013 and 2014 have been the worst years of all those analyzed, with 23% of the cases for the entire period. In fact, between 2003 and 2010 the number of municipalities affected by extortion decreased by 4%, between 2010 and 2014 the number of municipalities hit by this crime grew 82%, 86% of the 57 municipalities with more than 100 thousand inhabitants suffered from increases in extortion between 2010 and 2014, with an average growth of 354%. During the same period, the FARC increased the number of municipalities where they extort by 261%, going from 62 to 117 municipalities. Departaments with the highest rate of extortion per each 100 thousand inhabitants in 2014 were: Meta with 56.3, Casanare with 44.4, San Andrés with 34. Arauca with 25, Huila and Tolima with 22 and Caqueta with 21.